An introduction to economic dynamics - Shone, Ronald (Cambridge University Press, 2001)
An examples driven treatment of introductory economic dynamics for students with a basic familiarity of spreadsheets. Shone approaches the subject with the belief that true understanding of a subject can only be achieved by students themselves setting out a problem and manipulating it experimentally. Includes web-site for students and lecturers. Visit www.cambridge.org/resources/economics.